Physiological responses and performance characteristics of 200 m continuous swimming and 4X50m "broken" swimming with different interval time demands - Beidaris, N.; Botonis, P.; Platanou, T. (Biomechanics and Medicine in Swimming XI, 2010)
The purpose of the present study was to investigate the physiological responses and performance characteristics of ``broken`` swimming (4x50m) with different rest intervals (5, 10 and 20s) compared with those of continuous swimming (200m) during maximum intensity free-style swimming. Twelve voluntary swimmers of competitive level (aged: 14-17 years) were tested. Significant differences were observed in performance time and heart rate between continuous and «broken» swimming with resting interval of 20s (F=4.27, P=0.009 and F=3.31, P=0.03, respectively). However, no differences were found in blood lactate and oxygen consumption. In conclusion, it seems that even if the physiological responses were similar between conditions, the performance characteristics were higher in the condition of broken swimming with 20s resting interval.